2016
DOI: 10.1158/1055-9965.epi-16-0312
|View full text |Cite
|
Sign up to set email alerts
|

Metformin, Diabetes, and Survival among U.S. Veterans with Colorectal Cancer

Abstract: Background Metformin has been associated with improved CRC survival, but investigations are limited by small numbers of patients and confounding by diabetic severity. We examined the association between metformin use and overall survival (OS) in patients with diabetes and CRC in a large population of U.S. veterans, while adjusting for measures of diabetic severity. Methods Patients diagnosed with CRC from 1/2001-12/2008 were identified from the Veterans Affairs Central Cancer Registry. Multivariable models w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 58 publications
1
23
1
Order By: Relevance
“…In our meta-analysis, year of publication ranged from 2003 to 2016, and the regions included 2 American countries[7, 1315, 18, 19, 27, 30, 33, 37, 41, 42, 45, 46], 6 European countries[6, 11, 17, 28, 32, 39, 40, 44], 2 Asian countries[8, 9, 12, 16, 20, 29, 3436, 38, 43, 47] and 1 Oceania country[31]; the included studies contained 15 retrospective[9, 10, 14, 16–20, 27, 33, 36, 37, 39, 41, 47] and 21 prospective[68, 1113, 15, 2832, 34, 35, 38, 40, 4246] cohort studies; the sample size ranged from 391 to 1056243, and the mean age of study ranged from 46.4 to 72.07. In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our meta-analysis, year of publication ranged from 2003 to 2016, and the regions included 2 American countries[7, 1315, 18, 19, 27, 30, 33, 37, 41, 42, 45, 46], 6 European countries[6, 11, 17, 28, 32, 39, 40, 44], 2 Asian countries[8, 9, 12, 16, 20, 29, 3436, 38, 43, 47] and 1 Oceania country[31]; the included studies contained 15 retrospective[9, 10, 14, 16–20, 27, 33, 36, 37, 39, 41, 47] and 21 prospective[68, 1113, 15, 2832, 34, 35, 38, 40, 4246] cohort studies; the sample size ranged from 391 to 1056243, and the mean age of study ranged from 46.4 to 72.07. In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, …”
Section: Resultsmentioning
confidence: 99%
“…In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, 28, 29, 31, 3337, 3942, 4446] used the method of medical records, 5 studies[16, 20, 38, 43, 47] used the method of blood sugar test, and 6 studies[7, 10, 17, 27, 30, 32] used the method of self-reported. To avoid the effects of confounders, we preferred to extract the adjusted outcome effect estimates, but we still found that the outcome effect estimates of 4 studies were not adjusted.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 81 studies, and 8 observational studies 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 were included in this meta-analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies were all published in the past 4 years (2012–2016). Seven studies 19 , 20 , 21 , 22 , 24 , 25 , 26 reported the HR s for OS among CRC patients with T2DM, and four studies 19 , 21 , 23 , 25 reported the HR s for CS among CRC patients with T2DM. Of the included studies, four 19 , 20 , 22 , 23 were performed in Europe (Ireland, Netherlands, Denmark, UK), and three 21 , 24 , 26 in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…We appreciate the letter of Alam and colleagues, who underscore the point we made in our discussion section when we noted that time-related biases, such as immortal time bias, can threaten pharmacoepidemiologic studies of metformin as a potential chemotherapeutic agent (1). Vivid illustrations of this bias are available among prior metformin studies that defined exposure based on receipt of multiple prescriptions, with the interval of time between prescriptions being immortal, and discordant time zero definitions between comparison groups (2).…”
mentioning
confidence: 96%